Genetic scrambling as a defence against meiotic drive. - Haig, D; Grafen, A (1991)
Genetic recombination has important consequences, including the familiar rules of Mendelian genetics. Here we present a new argument for the evolutionary function of recombination based on the hypothesis that meiotic drive systems continually arise to threaten the fairness of meiosis. These drive systems act at the expense of the fitness of the organism as a whole for the benefit of the genes involved. We show that genes increasing crossing over are favoured, in the process of breaking up drive systems and reducing the fitness loss to organisms.